Adolescent problematic Internet use: Is a parental rating suitable to estimate prevalence and identify familial correlates?. (February 2017) - Wartberg, Lutz; Kriston, Levente; Bröning, Sonja; Kegel, Katharina; Thomasius, Rainer
Abstract: Background: High prevalence estimates for adolescent problematic Internet use have been reported. The objective of the present study was to estimate the prevalence of adolescent problematic Internet use first-time based on parental assessment instead of adolescents' ratings and additionally, to identify familial correlates. Methods: We investigated a representative sample of 1000 parents of adolescents (aged 12–17 years) with a standardized questionnaire measuring problematic Internet use and familial aspects. The statistical analyses were limited to 964 cases, because 36 of the adolescents have never used the Internet. To estimate the prevalence of problematic Internet use we conducted a latent class analysis. We used logistic regression analyses to identify familial correlates. Results: The prevalence estimate for adolescent problematic Internet use in Germany was 4.7% [95% Confidence Interval (CI): 3.4–6.1%]. Lower family functioning [Odds Ratio (OR): 0.66, CI: 0.55 to 0.78] and a higher frequency of parent-adolescent-conflicts (OR: 4.51, CI: 3.05 to 6.68) were associated with problematic Internet use. Conclusion: In an observational study, we found first indications that parental assessment can be suitable for estimating the prevalence of problematic Internet use in adolescents. With regard to familial correlates we found substantial accordance with results based on adolescents' self-reports. Highlights: All prevalence estimates of problematic Internet were based on self-assessments. In the present survey we used parental assessment instead of adolescents' ratings. We surveyed a representative sample of 1000 parents of adolescents (12–17 years). The prevalence estimate for adolescent problematic Internet use in Germany was 4.7%. Family functioning and familial conflicts were related to problematic Internet use.